The Bretton Woods institutions and the environment: Organizational learning within the World Bank and the International Monetary Fund (IMF) - Alexandra Lindenthal; Martin Koch (Administrative Sciences, 2013)
Due to a growing public awareness, in the last 40 years environmental impacts of development projects financed and supported by the World Bank and the International Monetary Fund (IMF) have come into view. Since then, the member states have pressured both organizations to implement environmental concerns. We analyze the reactions of the World Bank and the IMF's bureaucracies towards their principals' demands. To reveal if, and to what extent, the observed reactions of both bureaucracies towards environmental integration can be assessed as organizational learning, we develop in a first step a heuristic model that allows for a distinction between different levels of learning (compliant and non-compliant, single-loop and double-loop). In a second step we describe the efforts of the bureaucracies of the World Bank (from the 1970s until today) and the IMF (from the 1990s until today) to integrate environmental protection into their activities. Due to our interest in the quality of the organizational changes, we finally analyze if and to what extent the bureaucracies' reactions to the new external demand qualify as organizational learning. Furthermore, we discuss which factors helped or hindered organizational learning.
Keywords: 350; organizational learning; environmental integration; World Bank; IMF